2013
DOI: 10.1097/adm.0b013e3182a11ad0
|View full text |Cite
|
Sign up to set email alerts
|

Heroin or Conventional Opioid Maintenance? The Patients’ Perspective

Abstract: The data on the patients' perspective complement the existing clinical studies, showing that previously unresponsive opioid-addicted patients especially would switch to HMT, whereas most patients would prefer continuation of COMT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In particular, the authors found a greater reduction in the use of illicit heroin in patients receiving prescription diamorphine compared with control groups (Strang, Groshkova & Uchtenhagen, 2015). Also noteworthy, a recent Berlin-wide anonymous survey of patients under opioid services found that approximately 40% of those on conventional maintenance would prefer to transfer into diamorphine substitution (Bald, Bermpohl, Heinz, Gallinat & Gutwinski, 2013). Importantly, despite a higher opioid dose in terms of 'methadone equivalents', these patients reported more frequent use of illicit drugs than patients not desiring to switch to diamorphine maintenance therapy (Bald, Bermpohl, Heinz, Gallinat & Gutwinski, 2013).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In particular, the authors found a greater reduction in the use of illicit heroin in patients receiving prescription diamorphine compared with control groups (Strang, Groshkova & Uchtenhagen, 2015). Also noteworthy, a recent Berlin-wide anonymous survey of patients under opioid services found that approximately 40% of those on conventional maintenance would prefer to transfer into diamorphine substitution (Bald, Bermpohl, Heinz, Gallinat & Gutwinski, 2013). Importantly, despite a higher opioid dose in terms of 'methadone equivalents', these patients reported more frequent use of illicit drugs than patients not desiring to switch to diamorphine maintenance therapy (Bald, Bermpohl, Heinz, Gallinat & Gutwinski, 2013).…”
Section: Discussionmentioning
confidence: 92%
“…Also noteworthy, a recent Berlin-wide anonymous survey of patients under opioid services found that approximately 40% of those on conventional maintenance would prefer to transfer into diamorphine substitution (Bald, Bermpohl, Heinz, Gallinat & Gutwinski, 2013). Importantly, despite a higher opioid dose in terms of 'methadone equivalents', these patients reported more frequent use of illicit drugs than patients not desiring to switch to diamorphine maintenance therapy (Bald, Bermpohl, Heinz, Gallinat & Gutwinski, 2013). Finally, a positive association between patient satisfaction during methadone replacement therapy and treatment retention has been demonstrated, highlighting the great clinical relevance of this variable (Kelly, O'Grady, Mitchell, Brown & Schwartz, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Survey data concerning side effects, take-home treatment, and valuation of treatment have been previously published [ 28 – 31 ]. Anonymity of data was part of the ethical agreement.…”
Section: Methodsmentioning
confidence: 99%
“…Methadone as the most frequently provided opioid pharmacotherapy in MT is nowadays available in diverse modalities but fails to reach a considerable number of illicit opiate users [ 67 ]. Furthermore, Bald et al showed that a large number of patients in conventional OST would prefer HAT, in particular participants on higher dosages of methadone, with more than five detoxifications and continued illicit drug use [ 68 ]. Treatment study reviews of the 1990s pointed out that 30–70% of subjects leave methadone treatment within the first 2 years [ 69 , 70 ].…”
Section: Heroin-assisted Treatmentmentioning
confidence: 99%